STRATEGI KEPALA DESA DALAM MENINGKATKAN KINERJA PEGAWAI DI KANTOR DESA NAGARA KECAMATAN KIBIN KABUPATEN SERANG - Riyadil Jinan; Syamsul Hidayat; Saepudin Saepudin (Universitas Bina Bangsa, 2021)
The Village head is the highest authority in the village and as a formal or informal leader, a leader who is always in the midst of the people. The importance of employee performance in a government organization such as the Nagara Village Office is one element in achieving maximum service goals to the community. Of course, in this case the Nagara Village Head's Strategy is very influential on Employee Performance. However, it is inversely proportional to the performance of this Nagara Village Office employee. Performance that is not optimal will certainly affect services to the community. Of course, people are not satisfied with the services that have been provided by employees. The purpose of this study was to determine the Strategy of the Head of Nagara Village in improving Employee Performance at the Nagara Village Office, Kibin District, Serang Regency. The type of research used by researchers in this study is qualitative research with a descriptive approach based on phenomenological theory. The data collection tool or instrument is the researcher himself who goes directly to the field. Data collection techniques in this study are interviews, observation, documentation, literature. The informants in this study were from employees who worked at the Nagara Village Office, there were 4 informants, namely the Village Head as key informant, KAUR Planning, KASI Services and General KAUR. The results of this study are the Village Office internal routine meetings have been carried out well, although the time is uncertain, it can be once a week or once a month, the organizational structure already exists, the facilities and infrastructure are complete, related to employee discipline is good, for rewards and punishments there are only more benefits if there are employees who excel, the quality of human resources is good, there are already partnerships with other agencies, namely collaborating with the Department of Agriculture and training in the form of training with Village Consultative body.